Knowledge, risk perception and utilization of hepatitis B vaccine among youths in a semi-urban area in Ibadan, Oyo state, Nigeria - Oyasope, Beatrice Tomisin; Atibioke, Oluyemi Peter; Dipeolu, Isaac Oluwafemi (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Hepatitis B is a chronic liver disease responsible for high morbidity and mortality. Despite the availability of hepatitis B vaccine, the incidence of disease is increasing. This study was designed to investigate the knowledge, risk perception, and utilization of hepatitis B vaccine among youths in the Ido Local Government Area, Oyo state, Nigeria. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A cross-sectional survey design was adapted, and 422 consenting youths were recruited. A pre-tested semi-structured questionnaire was used for data collection. A 19-point knowledge scale was used; scores ≤6, >6–12, and >12– 19 were considered poor, fair and good knowledge, respectively. Risk perception was measured on a 14-point scale, with scores ≤7 and >7 as poor and good, respectively. Data were analyzed using descriptive statistics, Chi-square and Fisher’s exact at α0.05. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. Respondents were 26.6±3.5 years, and 56.2% were females. Only 13.7% had good knowledge of hepatitis B, and 53.2% had a good perception of hepatitis B infection. Moreover, 48.9% had received at least one dose of the Hepatitis B vaccine. A significant association existed between knowledge, risk perception and utilization of hepatitis B vaccine. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Knowledge and utilization of hepatitis B vaccine were low among the respondents. Health education programs in the study area are crucial to improving hepatitis B vaccine utilization among youth.